KOMUNIKASI TERAPEUTIK BIDAN DAN PASIEN PASCA MELAHIRKAN OPERASI PADA RUMAH SAKIT MUHAMMADIYAH PALANGKA RAYA - Ngalimun Ngalimun (Jurnal Terapung : Ilmu - Ilmu Sosial, 2019)
Therapeutic communication applied at the Islamic Hospital of Muhammadiyah Palangka Raya consists of four phases / stages, namely the pre-interaction phase, the action phase, the evaluation phase, and the documentation phase. In conducting therapeutic communication with patients, midwives use certain techniques such as recognizing and calling out the patient's name, giving greetings or greetings, shaking hands or touching, explaining medical actions to be taken, trying to find out the patient's condition through communication by giving patients the opportunity to explain his condition, pause for a moment, and ask related questions. The relationship between the midwife and the patient is important in therapeutic communication. Through a well-established relationship between the midwife and the patient, the midwife and the patient work together to achieve their goals. The goals of therapeutic communication include: helping patients to clarify and reduce the burden of feelings and thoughts, and can take effective action for patients. The therapeutic communication phases mainly consist of the pre-interaction phase, the action phase, the evaluation phase, and the documentation phase. Before meeting and conducting therapeutic communication to patients, a midwife needs to prepare herself before meeting with patients with different backgrounds and characters, while preparing themselves, midwives also study medical records of programs that have and will be implemented.Keywords: Therapeutic Communication, Midwives and Patients